A construct of the instrument for measuring junior high school mathematics teacher's self-efficacy - Rachmadi Widdiharto; Badrun Kartowagiran; Sugiman Sugiman (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2017)
The aim of this study was to develop a construct of the instrument for junior high school mathematics teacher self-efficacy and its mapping in the Special Region of Yogyakarta. The population was 816 junior high mathematics teacher and a sample of 274 teachers was selected through proportionate random sampling technique. The data were analyzed using Confirmatory Factor Analysis (CFA), using software Lisrel 8.80 through the first order and the second order stages. The result of data analysis toward four dimensions obtained: 11 fit items for dimension of personal efficacy (PE), 12 fit items for dimension of general teaching efficacy (GTE), 13 fit items for dimension of subject matter teaching efficacy (STE), and 8 fit items for dimension of outcome efficacy (OE). Afterward, the result of selecting 54 items in the first order stage was examined for the second order CFA which obtained Chi-Square = 297.58; df = 271; p-value = 0.12824; RMSEA = 0.019, which showed the model was fit to the data and obtained 25 fit items. The loading factors for each dimension PE, GTE, STE, and OE consecutively were: 0.46; 0.84; 0.89, and 0.92, and mapping of mathematics teacher self-efficacy level, which showed: 43.07% in low category, 55.47% in medium category (55.47%) and 1.46% in the high category.